The impact of the banking mergers on the banks performance in Sudan - Sharif, Emad Suleiman; Babeker, Mahtadi Abdullah (Journal of Economic, Administrative and Legal Sciences, 2018)
The purpose of this empirical study was to highlight the impact of the banking mergers on the banks performance in Sudan. Mergers aimed y to create Strong financial institutions that are able to compete domestically and internationally. The main problematic of this research is to measure the degree of success of the merger of Sudanese banks. especially، to assess the experience between farmers bank and attijare bank. Our hypotheses are bank capital، profits and deposits، increase after merger. We used the an analytical approach and descriptive approach. The results show that there is a very significant increase of the capital after the merger and in the same time profits and deposits increased.